Efficient Solvent Extraction of Phenol Using Imidazolium-Based Ionic Liquids - Imane Hamzi; Souad Bouchakour; Bachir Mostefa-Kara; Didier Villemin (Chemistry Proceedings, 2023)
Ionic Liquids (ILs) have gained significant attention in both industry and academia due to their unique properties and diverse applications. With countless possible combinations of cations (e.g., Ammonium, Sulfonium, Phosphonium) and anions (Organic or Inorganic), the variety of ILs is immense. Among them, Imidazolium salts form the largest IL family, making them a focal point in this study. Phenolic compounds, essential in the chemical industry, become hazardous to both human and aquatic life when released into the environment. Traditional separation methods for phenolics unfortunately involve environmentally problematic processes. This research focuses on synthesizing and characterizing Imidazolium-functionalized ILs ([EtO2C2mim]Br, [EtO2C2mim]BF4, [EtO2C2mim]PF6) and studying their phenol extraction abilities. The results revealed [EtO2C2mim]Br as the most effective, extracting 99% of phenol and offering a promising alternative for the efficient extraction of phenols from real coal liquefaction oil.